Facts and fallacies of purported ergogenic amino acid supplements - Williams, M. H. (Clinics in Sports Medicine, 1999)
Although current research suggests that individuals involved in either high-intensity resistance or endurance exercise may have an increased need for dietary protein, the available research is either equivocal or negative relative to the ergogenic effects of supplementation with individual amino acids. Although some research suggests that the induction of hyperaminoacidemia via intravenous infusion of a balanced amino acid mixture may induce an increased muscle protein synthesis after exercise, no data support the finding that oral supplementation with amino acids, in contrast to dietary protein, as the source of amino acids is more effective. Some well-controlled studies suggest that aspartate salt supplementation may enhance endurance performance, but other studies do not, meriting additional research. Current data, including results for several well-controlled studies, indicated that supplementation with arginine, ornithine, or lysine, either separately or in combination, does not enhance the effect of exercise stimulation on either hGH or various measures of muscular strength or power in experienced weightlifters. Plasma levels of BCAA and tryptophan may play important roles in the cause of central fatigue during exercise, but the effects of BCAA or tryptophan supplementation do not seem to be effective ergogenics for endurance exercise performance, particularly when compared with carbohydrate supplementation, a more natural choice. Although glutamine supplementation may increase plasma glutamine levels, its effect on enhancement of the immune system and prevention of adverse effects of the overtraining syndrome are equivocal. Glycine, a precursor for creatine, does not seem to possess the ergogenic potential of creatine supplementation. Research with metabolic by-products of amino acid metabolism is in its infancy, and current research findings are equivocal relative to ergogenic applications. In general, physically active individuals are advised to obtain necessary amino acids through consumption of natural, high-quality protein foods.